Review: performance of jujube and its extracts in cancer: therapeutic, toxicity-reducing and potentiating effects - Gou, Boyun; Chen, Guoqing; Huang, Shicong; Ning, Na; Gu, Qian; Duan, Shuai; Du, Yuhua; Nan, Yi; Yuan, Ling (Frontiers in Oncology, 2025)
Cancer is one of the most serious public health challenges in the world. The number of new and fatal patients with cancer continues to increase every year, which poses a serious threat to human health. Although there are effective treatments such as radiotherapy and chemotherapy for cancers, they are often accompanied by serious side effects. With the development of the pharmaceutical industry, there is a gradual desire to develop low-toxicity and effective anticancer drugs from traditional Chinese herbs. Due to its “homology of medicine and food,” jujube is one of the traditional Chinese herbs that is extensively used in China. In addition, jujube has received much attention around the world for its excellent pharmacological effects and food value. This article reviews the anticancer effects of a fruit, food, and drug, jujube, which have been shown in current studies, and analyzes its therapeutic mechanism, active ingredients, extraction and isolation methods, as well as its synergistic and attenuation performance in cancer. This will further promote the progress of natural medicine’s anti-cancer effect.